Análise da disposição final dos resíduos de construção e demolição na cidade de João Pessoa - Caldas, Ana Helena Mousinho (2016)
Waste resulting from the construction industry have a significant negative environmental impact, thus being a major problem for the construction industry and the regulatory agencies. The minimization of this waste can occur if they are properly managed from its generation to its final disposal, contributing to the reduction of environmental degradation. This research presents the results of the verification of the performance of the components of the RCD flow (generator - transporter - receiver for final disposal) regarding establishing legislation in the João Pessoa city. The aim of this study is to verify the compliance percentage (level of service) the final disposal stage of RCD flow in relation to the provisions of the legislation. The study presents the adherence percentage for the two companies officially responsible for the final disposal of this region, namely the USIBEN (RCD processing plant) which showed 79% of adherence and the Landfill Metropolitan which showed 63% adherence. The results show deviations in the treatment of RCD in relation to what is provided in legislation, especially to waste class D, which are considered dangerous, as well as other points that can and should be improved.